The Basic Understanding Of First Semester Students Of Mining Engineering About Commonly Used Mining Terminologies - Indri Lesta Siwidiani (Jurnal Teknologi Pertambangan, 2022)
Before being part of a certain department of a certain qualified college, one should prepare himself to look forward anything related to his dreamt department, at least knowing and understanding the commonly used terms related to that. when you have a dream being part of mining engineering department, you should know and understand about commonly used mining engineering. So, in this occasion, the author wants to know the first semester students of mining engineering understand about commonly used mining terms. The result of this little research indicates that the first semester students of mining engineering have good basic understanding and mastering about commonly used mining terms. It can be shown by the total number of the group which has answer type of A is about 73 members of the total population of 175, it’s about 41.7%. The group which has answer type of A is categorized having excellent answers, because the manner, attitude, tone, and language style that they show is very nice, chill out, but straight to the points. Their answers indicate that they understand and master the commonly used mining terms tested.